Some Integral Inequalities for the Polar Derivative of a Polynomial (Analysis in Theory and Applications, 2011)
If $P(z)$ is a polynomial of degree $n$ which does not vanish in $|z|
Keywords: polar derivative; polynomial; Zygmund inequality; zeros.